Interview with Daniel Scarpati, Filmmaker and Author of Gofers. Issue 3 (23rd March 2023) - Underwood, Gray
This is an interview with New York-based filmmaker/author Daniel Scarpati about his experiences working on set in various capacities and his writing/self-publishing process in creating Gofers, a guide to life on a film set and beyond for aspiring filmmakers and PAs.